Self-reported musculoskeletal disorders of the distal upper extremities and the neck in German veterinarians: a cross-sectional study. - Agnessa Kozak; Grita Schedlbauer; Claudia Peters; Albert Nienhaus (PLoS ONE)
Background Veterinary work is a physically demanding profession and entails the risk of injuries and diseases of the musculoskeletal system, particularly in the upper body. The prevalence of musculoskeletal disorders (MSD), the consequences and work-related accidents in German veterinarians were investigated. Work-related and individual factors associated with MSD of upper extremities and the neck were analyzed. Methods In 2011, a self-reporting Standardized Nordic Questionnaire was mailed to registered veterinarians in seven federal medical associations in Germany. A total of 3174 (38.4%) veterinarians responded. Logistic regression analysis was used to determine the association between risk factors and MSD-related impairment of daily activities. Results MSD in the neck (66.6%) and shoulder (60.5%) were more prevalent than in the hand (34.5%) or elbow (24.5%). Normal activities were affected in 28.7% (neck), 29.5% (shoulder), 19.4% (hand) and 14% (elbow) of the respondents. MSD in the upper body occurred significantly more often in large animal practitioners. Accidents that resulted in MSD were most frequently reported in the hand/wrist (14.3%) or in the shoulder (10.8%). The majority of all accidents in the distal upper extremities were caused by animals than by other factors (19% vs. 9.2%). For each area of the body, a specific set of individual and work-related factors contributed significantly to severe MSD: Older age, gender, previous injuries, BMI, practice type, veterinary procedures such as dentistry, rectal procedures and obstetric procedures as well as high demands and personal burnout. Conclusion From the perspective of occupational health and safety, it seems to be necessary to improve accident prevention and to optimize the ergonomics of specific tasks. Our data suggest the need for target group-specific preventive measures that also focus on the psychological factors at work.